HUBUNGAN KARAKTERISTIK PASIEN ISPA DAN TINGKAT KEPATUHAN MINUM OBAT DI APOTEK AR24 BATU AJI KOTA BATAM - Sri Hainil; Delladari Mayefis, Randy Rafael (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2021)
Upper respiratory tract infection is an infection of the upper or lower respiratory tract or acute inflammation of the upper to the respiratory tract caused by infection of the body or bacteria, viruses, or riketsia, without or accompanied by inflammation of the pulmonary parenchyma. The Ministry of Health recorded in 2007, the ISPA case amounted to 7.2 million, then increased to 18.7 million or approximately (5-6%) Of the total population of Indonesia in the year 2015. This research aims to know the relationship of characteristics of ISPA patients and the level of compliance with medicine at the Apotek AR-24 Batu Aji Batam City. The instrument used in this study is a questionnaire Compliance with drug use MMAS- 8 (Morisky Medication Adherence Scale). Based on the results of the compliance level of the questionnaire's response in 96 patients, patients with low compliance of 70 people (72.9%), moderate compliance of 26 people (27.1%). There is no significant link between each sample classification with P-value = 0.136 (not significant)